A Cerium(IV)–Carbon Multiple Bond1. Issue 49 (15th October 2013) - Gregson, Matthew; Lu, Erli; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; Liddle, Stephen T.
<x xml:space="preserve">Abstract</x> Straightforward access to a cerium(IV)–carbene complex was provided by one‐electron oxidation of an anionic "ate" cerium(III)–carbene precursor, thereby avoiding decomposition reactions that plague oxidations of neutral cerium(III) compounds. The cerium(IV)–carbene complex is the first lanthanide(IV)–element multiple bond and involves a twofold bonding interaction of two electron pairs between cerium and carbon.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>